2017
DOI: 10.1017/neu.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect the action of antidepressants in the forced swim test in Swiss mice

Abstract: Data suggest the lack of efficacy of orally administered bupropion, desipramine, fluoxetine in the FST in Swiss mice. High variability, due to high and low immobility mice, may explain the limited effects of the treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Changes to behavior and physiological responses to stressors may not be observable in subjects considered normal with respect to anxiety traits. In a recent study examining the effects of chronic oral treatment of SW mice with the antidepressants buproprion, desipramine, and fluoxetine, all failed to result in antidepressant-like behavior as measured in the FST (Suman et al, 2017 ). Indeed in another study measuring responses to chronic fluoxetine in a variety of mouse strains, a paradoxical increase in immobility in the TST was observed in the SW mice (Miller et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes to behavior and physiological responses to stressors may not be observable in subjects considered normal with respect to anxiety traits. In a recent study examining the effects of chronic oral treatment of SW mice with the antidepressants buproprion, desipramine, and fluoxetine, all failed to result in antidepressant-like behavior as measured in the FST (Suman et al, 2017 ). Indeed in another study measuring responses to chronic fluoxetine in a variety of mouse strains, a paradoxical increase in immobility in the TST was observed in the SW mice (Miller et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences between the groups in the results of the forced swim test performed on the second day, when it was considered that the mouse already had a good understanding of the test environment. It has been shown that immobility time increases 7 and 14 days after the initial test 33 . Further research is needed to investigate this phenomenon and its association with memory processes.…”
Section: Discussionmentioning
confidence: 99%
“…The level of carbolines was measured in the blood before and after death and in the organs [43,44,45,46]. The effects of β-carbolines on the living animal were most commonly tested behaviorally using the forced swim test, various types of the maze, and light/dark boxes [29,47,48,49].…”
Section: β-Carbolines In Experiments On Laboratory Animalsmentioning
confidence: 99%